The Role of the Uma Lengge Mengajar Community Reading Park in Increasing Children's Interest in Reading in Bima Regency - Ahmad, Ahmad; Amrin, Amrin (Yayasan Insan Mulia Bima, 2025)
The purpose of this study is to determine and analyze the role of the Uma Lengge Mengajar Community Reading Garden in Increasing Children's Reading Interest in Bima Regency. The research design used in this study is a case study with a qualitative research design. The data sources in this study include both primary and secondary data sources. Data collection techniques use three sources, namely, observation, interviews, and documentation. While the data analysis used is data analysis from Miles and Huberman, namely data reduction, data presentation, and conclusion. Based on the results of the study, the role of the Uma Lengge Mengajar Community Reading Garden in Increasing Children's Reading Interest in Bima Regency is by providing adequate human resources (HR), providing a literacy-based learning environment, creating creative and innovative programs, and building partnerships and community networks. Thus, the presence of the Uma Lengge Mengajar Community Reading Garden can provide positive and constructive contributions to increasing children's reading interest in Bima Regency